CLINICAL AND HORMONAL FEATURES OF PRECANCEROUS BREAST DISEASES IN WOMEN WITH OVARIAN DYSFUNCTION - Z.R. Kholdarova; D.Sh. Polatova (Journal of modern medicine, 2026)
Precancerous breast conditions in patients with ovarian dysfunction deserve particular attention because of the close physiological relationship between the reproductive and mammary systems. Impaired ovarian steroid hormone synthesis, relative or absolute estrogen excess, progesterone deficiency, and abnormalities in prolactin levels may stimulate cellular proliferation in breast tissue, thereby contributing to the development of persistent structural and functional changes.The primary objective of this study is to identify the specific clinical and hormonal characteristics of precancerous breast conditions in women with ovarian dysfunction and to evaluate the relationship between the type of ovarian disorder and the severity of pathological changes in the mammary glands. The diagnostic protocol includes a detailed assessment of medical history, evaluation of menstrual and reproductive status, determination of hormonal profile, and analysis of ultrasonographic, sonoelastographic, and mammographic findings. When clinically indicated, the diagnosis is confirmed by cytological or histological examination.A key aspect of the study is the assessment of serum estradiol, progesterone, prolactin, follicle-stimulating hormone (FSH), and luteinizing hormone (LH) levels, together with an analysis of their correlations with clinical and instrumental manifestations of the disease. Comparison of hormonal abnormalities with the characteristics of mastalgia, structural changes in glandular and connective tissues, the presence of cysts, and signs of proliferative activity makes it possible to distinguish different clinical and hormonal variants of the disease course.Such a comprehensive assessment of breast condition and ovarian function contributes to a more precise understanding of the pathogenetic mechanisms underlying the development of the pathology, facilitates the identification of patients at increased risk of disease progression, and provides a scientific basis for personalized strategies of dynamic follow-up and preventive correction.